Experiments in purchasing and supply management research. Issue 4 (December 2016) - Eckerd, Stephanie
Abstract: In this article, I provide a brief introduction to the use of experiments in purchasing and supply management research. Different types of experiments common within the field are introduced, and within these types I compare the strengths and weaknesses regarding reliability and validity concerns and the limitations surrounding participant pools. Topics for which experimentation is appropriate and useful are identified, and examples of recent work in the field provided. Several trends and future research opportunities are presented to inspire more work in this arena. Highlights: Article provides a brief introduction to the method of experiments and their usefulness in P/SM research. Benefits and limitations of experiments in general are discussed. Recent examples are highlighted, and opportunities and trends for future research are identified.